BALB/c Mice Vaccinated with Leishmania major Ribosomal Proteins Extracts Combined with CpG Oligodeoxynucleotides Become Resistant to Disease Caused by a Secondary Parasite Challenge. (26th January 2010) - Ramírez, Laura; Iborra, Salvador; Cortés, Jimena; Bonay, Pedro; Alonso, Carlos; Barral-Netto, Manoel; Soto, Manuel
Abstract : Leishmaniasis is an increasing public health problem and effective vaccines are not currently available. We have previously demonstrated that vaccination with ribosomal proteins extracts administered in combination of CpG oligodeoxynucleotides protects susceptible BALB/c mice against primary Leishmania major infection. Here, we evaluate the long-term immunity to secondary infection conferred by this vaccine. We show that vaccinated and infected BALB/c mice were able to control a secondary Leishmania major challenge, since no inflammation and very low number of parasites were observed in the site of reinfection. In addition, although an increment in the parasite burden was observed in the draining lymph nodes of the primary site of infection we did not detected inflammatory lesions at that site. Resistance against reinfection correlated to a predominant Th1 response against parasite antigens. Thus, cell cultures established from spleens and the draining lymph node of the secondary site of infection produced high levels of parasite specific IFN-γ in the absence of IL-4 and IL-10 cytokine production. In addition, reinfected mice showed a high IgG2a/IgG1 ratio for anti- Leishmania antibodies. Our results suggest that ribosomal vaccine, which prevents pathology in a primary challenge, in combination with parasite persistence might be effective for long-term maintenance of immunity.